Uptake and translocation of synthetic musk fragrances by pea plant grown in sewage sludge-amended soils. (1st October 2022) - Fernandes, Ana Sofia; Azevedo, Tomé; Rocha, Filipe; Nunes, Eugénia; Homem, Vera
Abstract: Sewage sludges are rich in organic matter and several essential nutrients for plant growth, making them very appealing for application in agricultural soils. However, they may also contain a wide range of emerging pollutants, which has raised concerns about the potential risks of this practice to crops, the environment, and public health - accumulation in soils and/or plant uptake and translocation of contaminants. Therefore, there is a need to study plant-soil interactions and assess the uptake potential of these contaminants by food crops to better understand these risks. The main aim of this work was to assess the possible drawbacks of sludge application to cropland, by observing the impact on the growth and yield of a model crop (pea plant - Pisum sativum ) grown over an 86-day greenhouse experiment and by assessing the uptake potential of synthetic musk fragrances. Different sewage sludge application rates (4–30-ton ha −1 ) and initial concentrations of contaminants were tested. The application of sludge yielded benefits to the cultivated plants, finding improved crop productivity with an application rate of 30-ton ha −1 . At the end of the experiment, soil samples and plants separated into sections were analysed using a QuEChERS extraction methodology followed by gas chromatography-mass spectrometry (GC-MS) quantification. Galaxolide (HHCB) and tonalide (AHTN) underwent uptake by the plant roots, having been detected in concentrations up to 346 ng g −1 on a dry weight basis (dw), but only HHCB was detected in above ground tissues. At the end, a decrease in the levels of synthetic musks in the amended soils (>80% in several instances) was observed. Assuming the worst-case scenario, no risk to human health was observed from the ingestion of peas grown on sewage sludge-amended soils. However, a soil hazard quotient analysis yielded worryingly high quotient values for AHTN in nearly all tested conditions. Graphical abstract: Image 1 Highlights: The application of sewage sludge to soils didn't hinder plant development. Galaxolide and tonalide underwent uptake by the plant roots (up to 346 ng g −1 dw). Only galaxolide was detected in above ground tissues (up to 6.90 ng g −1 dw). At the end, tonalide levels in the soil can cause environmental risk (HQ > 1). No risk was found for the levels detected in peas (HQ < 1).